THE EFFECT OF GREENWASHING ON BRAND EQUITY AND GREEN PURCHASE INTENTION AT GARNIER IN JAKARTA - Rahayu, Herawati; Saktiana, Galuh Mira (Graduate Program of Universitas Tarumanagara, 2023)
Climate change and global warming are causing various natural disasters. One of the causes is packaging waste from consumer-packaged goods products (in the form of food, drinks, and dairy products such as soap, cosmetics, etc.) which are difficult to decompose. Public awareness is needed to preserve the environment, one of which is by using environmentally friendly products such as Garnier through the